U-3: THE TRADITION OF LETTERS IN MYSTICAL LITERATURE IN THE CONTEXT OF NAQSHBANDI CHAIN: اد بیا ت تصو ف میں مکتو با ت کی رو ایتسلسلہ نقشبند یہ کے تنا ظر میں - Anwar Ullah; Abdul Rahman; Qari, Muhammad Akram (International Journal of Islamic Business, Administration and Social Sciences (JIBAS), 2023)
The early pioneers of Islamic preaching were the Companions (Allah be pleased with them) of the Holy Prophet (peace be upon him). Afterward, there came Sufis who spread the message of Islam. They did this wonderful job with sincerity and devotion. The Sufis used every medium at their disposal to convey the immortal message of Islam to the creatures of Allah, which was in tune with the modern requirements of the time. This research paper examines the preaching style of Naqshbandi Sufis. It also investigates how Naqshbandi Sufis used letters as an effective tool for social reform, spiritual training of the people, and Islam propagation. This article will help future researchers of mystical systems to research and analyze the various propagational aspects of current Sufi chains.